The existing business relations model has exhausted itself: restructuring on a scientific basis in the face of changes - I. D. Matskulyak; D. I. Matskulyak; N. Z. Nagdaliev (Вестник университета, 2022)
The article substantiates that the business relations functioning model has exhausted itself and in this connection there is an urgent need for society in a scientific approach to the market economy organisation. The methodology of the research proceeds from the unity of the historical and logical in the market economy development, the need to replace its obsolete forms with more developed ones, which is possible on the basis of modern economic science. The results include such methodological tasks as the material and technical base modernisation of the domestic economy, the business relations scientific organisation and the new intellectually advanced and mobile employee formation, as well as applied directions of their implementation in the scientific regulation form of these processes, taking into account the requirements of the socio-economic laws system and the updated state mission. Finally, the conclusion has been formulated about the need to accelerate the implementation of the proposed strategic and tactical directions of social development as objective measures proposed by modern economic science.